Measuring longitudinal beam parameters in the low energy section of the Oak Ridge Spallation Neutron Source accelerator - A. Shishlo; A. Aleksandrov; Yong Liu; Zhijun Wang (Physical Review Accelerators and Beams, 2018)
Knowledge of the longitudinal beam parameters is important for understanding beam dynamics in hadron linacs. Recently, a noninterceptive method suitable for measuring the longitudinal rms Twiss parameters in the high energy part of a hadron linac was developed and experimentally verified at the Spallation Neutron Source (SNS). This work presents an extension and modification of the method to allow measurements in the low energy part of a linac. Like the original method, amplitude of the beam rf harmonic measured by the beam position monitor is used to derive the information on the bunch length. The new method was tested at the medium energy beam transfer line of the SNS accelerator. The results are in good agreement with an independent measurement of the bunch length using the longitudinal acceptance scan of the drift tube linac. The suggested method is fast, and it can be a useful part of the initial longitudinal beam tuning at the front end of hadron linacs.